EQUIPMENT MAINTENANCE MANAGEMENT METHOD - OKUMURA HIRONOBU (2004)
PROBLEM TO BE SOLVED: To provide an equipment maintenance management method capable of easily specifying the equipment being the primary factor of the abnormality of a plurality in relevantly connected equipment, thereby quickly dealing with the abnormality. SOLUTION: In this method for carrying out the maintenance management of a plurality of equipment including equipment mutually connected so that one outputs can be turned to be the other inputs by using a management computer, the management computer executes reception processing to receive the information of whether or not the input and output of each equipment is normal and display processing to display whether or not the input and output of each equipment is normal based on the information. COPYRIGHT: (C)2004,JPO&NCIPI